Woody Plants of Kentucky and Tennessee : The Complete Winter Guide to Their Identification and Use - Jones, Ronald L. (Ronald Lee) (Book collections on Project MUSE., 2013)
For centuries, people have used trees, shrubs, and woody vines for food, clothing, ritual, construction, scientific study, and more. However, these important plants are easy to overlook during the winter months, when the absence of leaves, fruit, and other distinguishing characteristics makes them difficult to recognize. This comprehensive volume offers a guide to woody plants in Kentucky, Tennessee, and surrounding states during the winter season. Featuring color images of more than four hundred species, this botanical resource provides keys to the genera and species, as well as descriptions of the genera. The species accounts include useful information on Latin meanings, common names, habitats, and distributions, and notes on toxicity, nativity, rarity, and wetland status. In addition, the authors provide notes on practical uses for the plants, including food, medicine, fiber, and weapons.